Visualization and Analysis of the Danish 2006 Highly Pathogenic Avian Influenza Virus H5N1 Wild Bird Surveillance Data by a Prototype Avian Influenza BioPortal - Willeberg, Preben (2010)
Infection with highly pathogenic avian influenza virus H5N1 occurred for the first time in Denmark in 2006 during the last part of the European epidemic that mainly affected migrating wild birds. The total number of Danish wild bird cases was 45, of which only one was found through active surveillance using fecal sampling from resting areas for migrating species, whereas passive surveillance of dead wild birds provided 44 cases. One backyard, mixed poultry flock also became infected late in the epidemic. This study describes the spatial and temporal distribution of cases, initially characterized by a spatial-temporal cluster of affected tufted ducks that led to further spread to other wild bird species in the vicinity. The surveillance data also indicate an apparent die-off of the regional epidemic. As a tool in visualizing the spatial and temporal development of the epidemic, a prototype avian influenza (AI) BioPortal was used to provide online web-based access to the data. The AI BioPortal tools include mapping, graphing, phylogenetic tree construction, playback scenarios, and visualization of results of temporal-spatial analyses. Several of the features of this surveillance system compare favorably to the design of existing national and international surveillance information systems, and the AI BioPortal may become a useful tool for disease surveillance and for decision support in the event of future AI epidemics, both at national and international levels.